Mapeamento de QTL nos cromossomos 24 e 29 para medidas de peso, resistência a carrapato e estresse térmico em uma população F2 (Gir X Holandês) - Cervini, Marcelo (Universidade Federal de São Carlos, 2009)
In the latest years, Brazil became one of the most important countries regarding the production and exportation of animal-based food. Improvements on the sanitary conditions and animal research applied to animal production were some of the elements which have placed Brazil in this highlight position. However, difficulties on controlling the tick Rhipicephalus (Boophilus) microplus and herd management limitations concerning heat stress situations hamper a greater development on the national production. A significant part of the variation on these traits is controlled by many genes (Quantitative Trait Loci - QTL). The identification of loci influencing these traits is important for genetic improvement programs. The objective of this study was to identify and map QTL for tick resistance and heat stress tolerance in the chromosomes 24 and 29, as well as QTL related to growth traits in a F2 population (Gir x Holstein) by using the microsatellites scan methodology. No QTL was identified for the tick number found. However, on chromosome 24, an indicative QTL (P<0.10) for birth weight was identified. On chromosome 29, significant QTL for sweating rate (P<0.01) and respiration frequency (P<0.05) were also recognized. In addition, a suggestive QTL (P<0.05) for standardized weaning weight was found in chromosome 29 in one of the families. These results could help to improve the knowledge about the general factors affecting the evaluated traits, making possible the development of more efficient selection strategies for the environment conditions in the Brazilian production systems.
Keywords: Genética animal; Animais - melhoramento genético; QTL; Bovinos - parasitas.; CIENCIAS BIOLOGICAS::GENETICA